INFLUENCE OF ORGANIZATIONAL COMMUNICATION AND JOB ENGAGEMENT TO TEACHER SATISFACTION VOCATIONAL HIGH SCHOOL WEST CIKARANG DISTRICT - Rahmawati Rahmawati; Bedjo Sujanto; Siti Rochanah (Program Pascasarjana Universitas Negeri Jakarta, 2018)
This study aims to examine the influence of organizational communication and job involvement on teacher work satisfaction. This research was conducted at Vocational high School in West Cikarang sub-district through survey method with analysis of path analysis data. The sample of this study is 104 Teachers with civil servant status. The results showed that there are: 1) organizational communication Direct influence on job satisfaction; 2) job involvement Direct influence on job satisfaction; and 3) organizational communication Direct influence on job involvement. Thus, teacher job satisfaction is influenced by organizational communication and job involvement. This research recommends to the principal of Vocational high School in West Cikarang sub-district to apply good organizational communication in their environment and to fulfill the expectation for Vocational high School teachers to get job satisfaction well then teacher work involvement in school environment should be better. Keywords: organizational communication, job engagement, and job satisfaction.